Pengaruh Model Project Based Learning (PjBL) Berbantuan Teknik 3M dalam Pembelajaran Menulis Teks Cerpen Siswa Kelas X SMA Negeri 1 Batang Anai Kabupaten Padang Pariaman - Lumongga, Natasya; Rasyid, Yulianti (ALSYS, 2024)
The aim of this research is to describe the following things. First, to describe the learning to write short story texts for class X SMA Negeri 1 Batang Anai, Padang Pariaman Regency before using the Project Based Learning (PjBL) model assisted by 3M techniques. Second, to describe the learning to write short story texts for class X students of SMA Negeri 1 Batang Anai, Padang Pariaman Regency after using the Project Based Learning (PjBL) model assisted by 3M techniques. Third, to describe the influence of the Project Based Learning (PjBL) model assisted by 3M techniques in learning to write short story texts for class X students at SMA Negeri 1 Batang Anai, Padang Pariaman Regency. There are three results of this research. First, the learning to write short story texts for class Second, the learning to write short story texts for class Third, based on the results of the t-test, it was concluded that there was a significant influence on the use of the Project Based Learning (PjBL) model assisted by 3M techniques in learning to write short story texts for class ) at the α significance level of 0.05 and a confidence level of 95%. This shows that there is a significant influence in the use of Project Based Learning (PjBL) assisted by 3M techniques in learning to write short story texts for class X SMA Negeri 1 Batang Anai Padang Pariaman Regency.